Anatomy of the New Testament : a guide to its structure and meaning - Spivey, Robert A.; Smith, D. Moody; Black, C. Clifton (Fortress Press, 2013)
This broadly adopted textbook weds literary and historical approaches to focus on the New Testament's structure and meaning. Anatomy of the New Testament is systematic, critical, and reliable in its scope and content. This seventh edition has been revised throughout, to take account of current trends in scholarship and to discuss important interpretative issues, such as the Gospel of Thomas. Each chapter includes two new features: Have You Learned It? offering questions for analysis and synthesis; What Do They Mean? presenting definitions of key terms to enhance student comprehension and cri.